A new species of Duttaphrynus (Anura : Bufonidae) from Northeast India - Das, Abhijit; Chetia, Mitali; Dutta, Sushil Kumar; Sengupta, Saibal (Zootaxa, 2013)
A new species of montane toad Duttaphrynus is described from Nagaland state of Northeast India. The new species is diagnosable based on following combination of characters: absence of preorbital, postorbital and orbitotympanic ridges, elongated and broad parotid gland, first finger longer than second and presence of a mid-dorsal line. The tympanum is hidden under a skin fold (in male) or absent (in female). The species is compared with its congers from India and Indo- China. We propose to consider Duttaphrynus wokhaensis as junior synonym of Duttaphrynus melanostictus.